The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1021/je049586l
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical and Theoretical Studies of Dimethylpyridine-2,6-dicarboxylate and Pyridine-2,3-, Pyridine-2,5-, and Pyridine-2,6-dicarboxylic Acids

Abstract: The standard (p°) 0.1 MPa) molar enthalpies of formation for gaseous pyridine-2,5-dicarboxylic acid, pyridine-2,6-dicarboxylic acid, and dimethylpyridine-2,6-dicarboxylate were derived from the standard molar enthalpies of combustion, in oxygen, at T ) 298.15 K, measured by static bomb combustion calorimetry, and the standard molar enthalpies of sublimation, at 298.15 K, measured by Calvet microcalorimetry: pyridine-2,5-dicarboxylic acid, -(580.6 ( 5.0) kJ‚mol -1 ; pyridine-2,6-dicarboxylic acid, -(608.0 ( 6.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
(64 reference statements)
6
11
0
Order By: Relevance
“…Recently, Roux et al 35 reported an enthalpic increment of (18.0 ( 4.6) kJ‚mol -1 for the methylation of benzoic acid, which is in good agreement with the increment for the dimethylation of pyridine-2,6-dicarboxylic acid. 12 The present results point to a similar increment for the methylation of 4-pyridine carboxylic acid and to a higher increment for the methylation of 2-pyridine carboxylic acid. This should reflect the effect of the intramolecular hydrogen bond in 2-pyridine carboxylic acid described by Shahawy et al 36 on the basis of theoretical SCF-CI calculations.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Recently, Roux et al 35 reported an enthalpic increment of (18.0 ( 4.6) kJ‚mol -1 for the methylation of benzoic acid, which is in good agreement with the increment for the dimethylation of pyridine-2,6-dicarboxylic acid. 12 The present results point to a similar increment for the methylation of 4-pyridine carboxylic acid and to a higher increment for the methylation of 2-pyridine carboxylic acid. This should reflect the effect of the intramolecular hydrogen bond in 2-pyridine carboxylic acid described by Shahawy et al 36 on the basis of theoretical SCF-CI calculations.…”
Section: Resultssupporting
confidence: 82%
“…In this context, systematic experimental and theoretical thermochemical studies on heterocyclic molecules derived from pyridine have been done in our Thermochemistry Laboratory for more than a decade in order to evaluate the energetic effects of different substituents on the pyridinic ring. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The main goal of the present work is to determine the gaseous enthalpies of formation of methyl picolinate (2-PyCOOCH 3 ), methyl nicotinate (3-PyCOOCH 3 ), and methyl isonicotinate (4-PyCOOCH 3 ), represented in Figure 1, together with the measurement of other relevant properties to the thermodynamic characterization of those isomers.…”
Section: Introductionmentioning
confidence: 99%
“…What are the relative stabilities of the isomeric diacetylpyridines? Is it the same order as recently found for the related pyridinedicarboxylic acids [84] wherein COOH replaces COCH 3 ?…”
Section: Issuesupporting
confidence: 67%
“…The structure of this zinc(II) complex revealed the peculiarity of having the ethylenediamine ligand acting in a very unusual way as a bridge. The enthalpy of formation of dipicolinic acid has been recently determined as well as its 2,3-and 2,5-isomers [110].…”
Section: Issuementioning
confidence: 99%
“…We wonder what is the case for the isomeric pyridine-3,4-dicarboxylate chelate derivative? Comparison between the 2,3-and 3,4-diacids has surprisingly been lacking: for example, the enthalpy of formation of only the former has been measured [110].…”
Section: Issuementioning
confidence: 99%